Development of an in-situ signal amplified electrochemical assay for detection of Listeria monocytogenes with label-free strategy. (1st October 2021) - Chen, Qiming; Yao, Chenhui; Yang, Cuiyun; Liu, Zhanmin; Wan, Sibao
Highlights: No labeled primers required. G-quadruplex sequences were generated while LAMP amplify targeted gene sequences. The whole detection process could be finished in 2 h. The detection assay had a detection limit of 6.8 CFU/mL. Abstract: Listeria monocytogenes is an important foodborne pathogen, which imposes great burdens on public health. The current methods for detecting L. monocytogene are limited in several ways such as time consuming and lab equipment dependent. In this study, we developed a new electrochemical assay to improve the efficacy. This assay allows us to generate numerous G-quadruplex sequences while loop-mediated isothermal amplification happens. Then, these G-quadruplex sequences form DNAzyme to produce a color change and an electrochemical signal by oxidizing tetramethylbenzidine. This assay could be finished in 2 h, which significantly reduced the detection time. Also, we confirmed the limit of detection of this assay at 6.8 CFU/mL according to 3σ criterion. Our assay shows good sensitivity to detect bacteria range from 52.5 to 5.25 × 10 4 CFU/mL. This assay's reliability was also confirmed by detecting artificially contaminated pork samples. Thus, we propose this electrochemical assay for rapid and sensitive detection of L. monocytogenes in food.